Preliminary Report On First Database Of Useful Protein Substances From Discus Fish Epidermal Mucus (Symphysodon Spp.) Utilizing The Proteomics Platform. - Chong, KK; Foo, J; Lam, TJ; R, Hashim; Chong, ASC (2004)

(untitled)
Many times, fish epidermal mucus has been reported as an essential component for fishes in the area such as mechanical protection, gas transportation, and osmoregulation (Shephard, 1994). Discus fish is a cichlid species demonstrating fry feeding behavior via the parental mucus secretion (Noakes and Barlow, 1972). This species also an important ornamental species with global trading status and is currently being produced locally.